Financial inclusion and fintech: a state-of-the-art systematic literature review - Dao Ha; Phuong Le; Duc Khuong Nguyen (Financial Innovation)
Abstract This study presents an all-inclusive analysis of the literature on the augmentation of financial inclusion through fintech. Ninety-six papers were selected from the 2951 articles in the Web of Science, Scopus, and EBSCO databases. This study uses bibliometric and content analysis techniques to illuminate the underexplored aspects of fintech’s impact on financial inclusion. Unlike previous studies, this study consolidates a significant amount of the literature on financial inclusion by systematically contextualizing theories and viewpoints from the fintech sector. The key findings include the identification of three main research clusters: (1) the advent of novel services, (2) the transformation of the market landscape, and (3) the roles of stakeholders in the fintech ecosystem. The analysis reveals gaps in the existing research, such as the need for more studies on the tangible impact of fintech on financial inclusion and regulation. This study concludes by highlighting potential directions for future research and emphasizing the importance of policymakers paying greater attention to fintech’s implications for financial inclusion.